A proposed educational unit in the university skills course to develop project management skills among Jeddah university students in accordance with Kingdom's Vision 2030 and the requirements of its success from the point of view of the faculty members - Al Owidy, Nahed Adel (Journal of Educational and Psychological Sciences, 2021)
The study aimed to explore the feasibility and feasibility of a proposed educational unit in the university skills course to develop project management skills among Jeddah university students in accordance with The Kingdom's Vision 2030 and the requirements of its success from the point of view of faculty members in Jeddah province.In order to achieve some of the objectives of The Kingdom's Vision 2030 for renewal in the higher education system, one of the goals of Vision 2030 is to reform the Saudi economy, continue its growth and end its dependence on oil as the main source of income, the study adopted the descriptive analytical approach and used a questionnaire from a sample of (50) faculty members at Jeddah University, and the study reached the following results: identified important project management skills that should be included for the proposed educational unit in the university skills course and appropriate for university education. The skill of applying the steps of project-building, theoretical knowledge and then practical application (96%), project implementation skills (96%), skill of preparing a feasibility study (90%), and elements of project management (88%), achieving the proposed educational unit for some of the objectives of the Kingdom's vision 2030, showed that 90% of faculty members agree that the proposed educational unit in the University Skills Course at Jeddah University achieves some of the objectives of the Kingdom's vision 2030 m, and the results showed that the strategies of education appropriate in teaching are appropriate in teaching. The study recommends decision makers and interested saudi university administrators to renew curricula, develop courses that help graduates work, promote the economy, solve the problem of unemployment and low salaries by providing the addition of the educational unit in a university course that is taught in the preparatory year to support skills in different disciplines with knowledge to apply small and medium-sized projects, and we suggest adding the educational unit in the course of employment and the lack of salaries by providing the addition of the educational unit in the university skills course, which is taught in the preparatory year to support skills in different disciplines with knowledge to apply small and medium-sized projects, and we suggest adding the educational unit in the course of the semi-experimental research as a semi-experimental experience. To obtain the impact of this proposed course on Jeddah university students and the work they can work on.
Keywords: Project Management; Educational Unit; Kingdom Vision 2030